Comparing the education gradient in chronic disease incidence among the elderly in six OECD countries - Aurelie Côté-Sergent; Raquel Fonseca; Erin Strumpf, (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2018)
Inequalities in health by educational attainment are persistent both over time and across countries. However, their magnitudes, evolution, and main drivers are not necessarily consistent across jurisdictions. We examine the health-education gradient among older adults in the United States, Canada, France, the Netherlands, Spain and Italy, including how it changes over time between 2004 and 2010. Using longitudinal survey data, we assess how rates of incident poor health, incident difficulties with activities of daily living, and incident chronic conditions vary by educational attainment across countries. We also examine how potential confounders, including demographic characteristics, income, health care utilisation and health behaviours, affect the health-education gradient within countries over time. We find systematic differences in disease incidence, as well as in the health-education gradients, across countries. We also demonstrate that while adjusting for confounders generally diminishes the health-education gradient, the impacts of these variables vary somewhat across countries.
Keywords: 330